2020
DOI: 10.15406/mojph.2020.09.00328
|View full text |Cite
|
Sign up to set email alerts
|

A review of environmental, social and health impact assessment (Eshia) practice in Nigeria: a panacea for sustainable development and decision making

Abstract: Local participation is always beneficial for sustainable action and environmental problems resulting from urban implementation due to the failure of social and institutional change necessary for a successful transformation of rural life to urban life ahead of the rapid movement of the population. Despite good legal practice and comprehensive guidelines, evidence suggests that Environmental Impact Assessment (EIA) or more broadly Environmental, Social and Health Impact Assessment (ESHIA) have not yet been found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Surface soil and vegetation are considered as major sink of airborne metals. Consequently, the measurement of metals in these media can be useful to establish trends and abundance and their consequences as a result of natural changes and those caused by man [87][88][89][90][91][92][93][94]. Of the two environmental matrices, the soil has largely been used to establish metal contamination in relation to natural or anthropogenic in uence on the environment [18,48].…”
Section: 3: Heavy Metal Content Of Uncontaminated Soil and Cement-con...mentioning
confidence: 99%
“…Surface soil and vegetation are considered as major sink of airborne metals. Consequently, the measurement of metals in these media can be useful to establish trends and abundance and their consequences as a result of natural changes and those caused by man [87][88][89][90][91][92][93][94]. Of the two environmental matrices, the soil has largely been used to establish metal contamination in relation to natural or anthropogenic in uence on the environment [18,48].…”
Section: 3: Heavy Metal Content Of Uncontaminated Soil and Cement-con...mentioning
confidence: 99%
“…Demkova, et al (2022) demonstrated that sustainable development aims to meet the present needs of a community without compromising the ability of future generations to meet their own needs. Scholars like Raimi (2020) and Chan (2021) have emphasized the importance of participatory approaches in community development, where community members actively engage in planning and decision-making processes. Additionally, the United Nations' Sustainable Development Goals (SDGs) have placed a strong emphasis on community engagement and partnerships as critical factors in achieving sustainable development.…”
Section: Community Development Initiatives and Sustainable Developmentmentioning
confidence: 99%
“…Furthermore, the study draws upon the principles of sustainable development, a widely recognized theoretical framework that emphasizes the importance of meeting the needs of the present without compromising the ability of future generations to meet their own needs (Echendu, 2020;Raimi, 2020;Ajor, et al 2023). Sustainable development theory guides the examination of whether the community development initiatives in Awgbu are designed and implemented in a manner that ensures long-term environmental, social, and economic sustainability.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Soil contamination by crude oil poses a formidable environmental challenge, with profound implications for ecosystem health and human well-being (Ayibatonye et al, 2024a, b;Omoyajowo et al, 2024;Saliu et al, 2023;Raheem et al, 2023;Kader et al, 2023a, c;Raimi et al, 2022a, b;Ifeanyichukwu et al, 2022;Raimi and Odubo, 2022;Deinkuro et al, 2021a, b;Olalekan et al, 2021;Okoyen et al, 2020;Olalekan et al, 2019b;Premoboere and Raimi, 2018;Raimi and Sabinus, 2017a). The persistence of hydrocarbons in soil matrices disrupts microbial communities, impeding crucial nutrient cycling processes and heightening the risk of groundwater contamination (Raimi et al, 2023;Olalekan et al, 2023;Glory et al, 2023;Kader et al, 2023b;Stephen et al, 2023;Stephen et al, 2022;Awogbami et al, 2022;Raimi et al, 2022c, d, e;Afolabi and Raimi, 2021;Raimi et al, 2021;Afolabi and Morufu, 2021;Morufu et al, 2021a, b, c;Olalekan et al, 2020;Olalekan et al, 2019a;Raimi et al, 2019d;Raimi, 2019;Olalekan et al, 2018;Morufu and Clinton, 2017;Raimi and Sabinus, 2017b). Urgent action is required to develop effective remediation strategies (Alaidaroos, 2023;Morufu et al, 2021d;Adedoyin et al, 2020;Raimi et al, 2020a;…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of hydrocarbons in soil matrices disrupts microbial communities, impeding crucial nutrient cycling processes and heightening the risk of groundwater contamination (Raimi et al, 2023;Olalekan et al, 2023;Glory et al, 2023;Kader et al, 2023b;Stephen et al, 2023;Stephen et al, 2022;Awogbami et al, 2022;Raimi et al, 2022c, d, e;Afolabi and Raimi, 2021;Raimi et al, 2021;Afolabi and Morufu, 2021;Morufu et al, 2021a, b, c;Olalekan et al, 2020;Olalekan et al, 2019a;Raimi et al, 2019d;Raimi, 2019;Olalekan et al, 2018;Morufu and Clinton, 2017;Raimi and Sabinus, 2017b). Urgent action is required to develop effective remediation strategies (Alaidaroos, 2023;Morufu et al, 2021d;Adedoyin et al, 2020;Raimi et al, 2020a;Ajayi et al, 2020;Olalekan et al, 2020b, c;Suleiman et al, 2019;Omidiji and Raimi, 2019). Bioremediation has emerged as a promising solution, harnessing the metabolic prowess of microorganisms to degrade hydrocarbons and restore soil functionality (Deinkuro et al, 2021a, b;Glory et al, 2023;Raimi and Sabinus, 2017a).…”
Section: Introductionmentioning
confidence: 99%